Photocatalytic Degradation of Phenol Using Immobilized TiO2 Nanotube Photocatalysts - Chung Leng Wong; Yong Nian Tan; Abdul Rahman Mohamed (Journal of Nanotechnology)
TiO2 nanotubes immobilized on silica gel were used in the photocatalytic degradation of phenol in a batch reactor. The highest rate of photocatalytic activity was observed when the ratios of TiO2 nanotubes: silica gel: colloidal silica were 3 : 2 : 20. The optimal air flow rate for phenol degradation was 0.3 L/min while pH 3 was optimal for the reaction medium. Decreasing the initial phenol concentration led to an increase in phenol degradation efficiency due to more hydroxyl radicals being presented on the catalyst surface. Immobilized TiO2 nanotubes showed higher photocatalytic activity than that of the pure TiO2 which only achieved 87% degradation. Compared with pure TiO2, the immobilized TiO2 nanotubes benefited from a larger specific surface area and a low recombination rate of photogenerated electron-hole pairs. After three operating cycles, the decrease in photocatalytic activity of the immobilized TiO2 nanotubes was slight, indicating that the immobilized TiO2 nanotubes have excellent stability and reusability.